Antibacterial drugs in the form of sprays for the topical treatment of pyodermas and dermatoses complicated with a secondary infection - YE. V. Matushevskaya (Vestnik Dermatologii i Venerologii, 2017)
The article covers issues related to the application of topical antibacterial drugs for the treatment of pyodermic skin diseases. The author describes mechanisms of action and advantages of the topical form of antibiotics and GCS for the topical treatment of pyodermas. The article substantiates indications for the administration of topical GCS drugs in a combination with antibacterial drugs. The efficacy and safety of antibacterial and combination topical drugs such as Neomycin, Oxycort and Polcortolon TC in the form sprays for the treatment of pyodermas and complicated forms of chronic dermatosis.